2015
DOI: 10.3109/17482941.2014.994642
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ views of consent for research enrollment during acute myocardial infarction

Abstract: This study demonstrates that patients recognize barriers to understanding but value elements of consent. Further research is needed to develop approaches that meet patients' goals while recognizing the limitations inherent to this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…This may have been driven by lower representation of behavioral studies in the acute setting, and behavioral studies’ lower acceptance rates may be a result of the fact that they often require greater “agency” on the part of the participant. However, an increased rate of acceptance in acute studies also coheres with observations that decision making and the nature of consent likely differ in more‐acute settings . Specifically, the presence of significant time pressure, stress, and physical symptoms likely limits patients’ understanding of clinical trials for which they are eligible and may change the nature of their decision making.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This may have been driven by lower representation of behavioral studies in the acute setting, and behavioral studies’ lower acceptance rates may be a result of the fact that they often require greater “agency” on the part of the participant. However, an increased rate of acceptance in acute studies also coheres with observations that decision making and the nature of consent likely differ in more‐acute settings . Specifically, the presence of significant time pressure, stress, and physical symptoms likely limits patients’ understanding of clinical trials for which they are eligible and may change the nature of their decision making.…”
Section: Discussionmentioning
confidence: 70%
“…However, an increased rate of acceptance in acute studies also coheres with observations that decision making and the nature of consent likely differ in more-acute settings. 11,12 Specifically, the presence of significant time pressure, stress, and physical symptoms likely limits patients' understanding of clinical trials for which they are eligible and may change the nature of their decision making. Second, markedly different acceptance between Western Europe and the United States underscores perceptions that cultural factors play a role in enrollment decisions and highlights the need to expand education in the United States regarding the importance of trials to health system improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Two surveys found that most patients prefer to give consent for standard-of-care trials in less acute situations (13,14). Even patients who recognize the limitations inherent in obtaining consent in the emergency setting report that they want to have a say in whether they are enrolled in research (15,16). And patients sometimes decline to enroll in acute care trials, suggesting that some patients may not want to participate in emergency care trials.…”
Section: Discussionmentioning
confidence: 99%
“…1 10 Field testing was conducted with 11 eligible participants; these interviews were excluded from analysis. Consistent with the qualitative and quantitative aims of this study, interviews contained both closed-ended and open-ended questions.…”
Section: Methodsmentioning
confidence: 99%